HUBUNGAN DAYA LEDAK OTOT TUNGKAI DENGAN KECEPATAN TENDANGAN SABIT PADA ATLET PUTRA PENCAK SILAT WALET PUTI PEKANBARU - Nini Haryati; Ramadi '; Kristi Agust (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The problem in this research was is still lack of speed crescent kick in pencak silat athletes sons walet puti Pekanbaru. It is suspected lack of leg muscle explosive power at the time of the crescent kick. The purpose of this study to determine the correlation of leg muscle explosive power with the speed of a crescent kick. This is correlational study that aimed to know how big the contribution between independent and dependent variabels. After that, conducted data normality test by Liliefors test with significant level α = 0.05, and the result for normality test of variable X, L0maks (0,168) < Ltable (0,258), the normality test of variable Y, L0maks (0,134) < Ltable (0,258), in other words the distribution of the data is normal. Then continued to found r used product moment correlation analysis, if rresult > rtable so it was have significant correlation. The result of this research showed: it was significant correlation between leg muscle explosive power with the speed of a crescent kick, rresult (0,727) > rtable (0,666). The conclusion was have significant correlation between leg musle explosive power with speed crescent kick in pencak silat athletes sons walet puti Pekanbaru.Keywords: Correlation, Explosive power leg muscle, Speed crescent kick